Tranexamic Acid in Chronic Subdural Hematomas (TRACS): study protocol for a randomized controlled trial. Issue 1 (December 2016) - Iorio-Morin, Christian; Blanchard, Jocelyn; Richer, Maxime; Mathieu, David
Abstract Background Chronic subdural hematoma (CSDH) is one of the most frequent reason for cranial neurosurgical consultation. There is no widely accepted medical treatment for this condition. Herein, we present the protocol for the Tranexamic Acid (TXA) in Chronic Subdural Hematomas (TRACS) trial aiming at determining whether TXA can increase the rate of CSDH resolution following conservative management, lower the number of required surgical procedures and decrease the rate of CSDH recurrence following surgical evacuation. Methods TRACS is a multicenter, double-blind, randomized, parallel-design, placebo-controlled, phase IIB study designed to provide preliminary efficacy data as well as feasibility, safety and incidence data required to plan a larger definitive phase III trial. Consecutive patients presenting with a diagnosis of chronic subdural hematoma will be screened for eligibility. Exclusion criteria include: specific risk factors for thromboembolic disease, anticoagulant use or contraindication to TXA. A total of 130 patients will be randomized to receive either 750 mg of TXA daily or placebo until complete radiological resolution of the CSDH or for a maximum of 20 weeks. CSDH volume will be measured on serial computed tomography (CT) scanning. Cognitive function tests, quality of life questionnaires as well as functional autonomy assessments will be performed at enrollment, at 10 weeks following randomization and at 3 months following treatment cessation. During the treatment period, patients will undergo standard CSDH management with surgery being performed at the discretion of the treating physician. If surgery is performed, the CSDH and its outer membrane will be sampled for in vitro analysis. The primary outcome is the rate of CSDH resolution by 20 weeks without intervening unplanned surgical procedure. Secondary outcomes include: CSDH volume, incidence of surgical evacuation procedures, CSDH recurrence, cognitive functions, functional autonomy, quality of life, incidence of complications and length of hospital stay. Planned subgroup analyses will be performed for conservatively versus surgically managed subjects and highly versus poorly vascularized CSDH. Discussion CSDH is a frequent morbidity for which an effective medical treatment has yet to be discovered. The TRACS trial will be the first prospective study of TXA for CSDH. Trial registration NCT ID:NCT02568124 .